Estimating Measurement Accuracy in Modern Quantum Architectures - Marek WRÓBLEWSKI; Andrzej OBUCHOWICZ (Communications of International Proceedings, 2025)
This article presents the current capabilities for measuring the accuracy of selected IBM Q-class quantum architectures for specific stages and tasks of the recommendation process in hybrid classical-quantum recommendation systems. The main motivations for this research undoubtedly include the increased use of quantum technologies to accelerate the computational process in recommendation systems, as well as the need to assess the utility of available quantum processors for tasks requiring high accuracy. A comparison of the implementation of complex multi-qubit systems in a quantum simulator with that on a real quantum computer is discussed to demonstrate the measurement accuracy of currently available quantum architectures and the error rate compared to simulations of near-ideal systems. The literature lacks consistent comparative analyses that compare real implementations of multi-qubit systems on real quantum computers with their ideal simulations. The existing works mainly focus on model examples or theoretical analyses, which leaves a gap regarding the estimation of the actual error rate and stability of the performed calculations in recommendation applications. This motivated the presentation of important aspects of error generation and the identification of their causes.
Keywords: Quantum computer; qubit; quantum circuits; recommendation systems; decoherence